Analysis of VinFast’s Strategy to Enter the Indonesian Market through the Creation of a Business Ecosystem and Value Chain - Margareth Yosevine, Anne (Yayasan Pendidikan Belajar Berdikari, 2026)
The development of the electric vehicle (EV) industry in Indonesia has shown a significant upward trend in line with the government’s commitment to energy transition and carbon emission reduction. VinFast, an electric vehicle manufacturer from Vietnam, views Indonesia as a strategic market in Southeast Asia as well as a foundation for long-term electric vehicle ecosystem development. This study aims to analyze VinFast’s strategy in penetrating the Indonesian market through the creation of a business ecosystem and the strengthening of its value chain. This research adopts a qualitative descriptive approach using the Global Marketing Strategy (GMS), Segmenting–Targeting–Positioning (STP), and Porter’s Value Chain frameworks. Primary data were obtained through in-depth interviews with managerial-level informants at PT VinFast Trading Indonesia (VFID), while secondary data were collected from documentation and relevant literature. The findings indicate that VinFast implements a hybrid strategy by combining global standardization of core EV technology with local adaptation in pricing, distribution, after-sales services, and ecosystem collaboration to build trust and accelerate EV adoption in Indonesia.